Exposure profiles and predictors of a cocktail of environmental chemicals in Chinese men of reproductive age. (July 2022) - Yang, Pan; Wang, Jie; Hong, Ao-Bo; Huang, Li-Li; Xie, Qi-Tong; Wang, Yi-Xin; Xiong, Cheng-Liang; Meng, Tian-Qing; Pan, An; Chen, Da
Abstract: Personal care products, such as additives, have raised widespread concerns about the potential threat to male reproductive health. The spermatogenesis in humans lasts for approximately 90 days, the average levels of these chemicals remain unclear during spermatogenesis. In our study, we pooled urine samples from each man during the days of 1–15, 16–31, 32–63, and ≥64, and examined exposure to 48 typical additive chemicals. By principal component analysis (PCA), k-means clustering, and Spearman's rank correlations, we then identified 6 PC scores and 4 clusters based on profiles of these chemicals. Some industrial, commercial or structural similar chemicals (e.g., phthalates) were significantly correlated compared to unrelated chemicals (e.g., benzophenone). PCA scores were associated with individual lifestyles (e.g., household income, tea consumption, and drinking tap water). Distinct exposure components and exposure patterns of personal care products may help the reproductive health assessment of men. We suggested more concerns for widespread exposure to these chemicals for men. Graphical abstract: Image 1 Highlights: Typical additive chemicals are exposed to men of reproductive age. Six PC scores and four clusters were characterized profiles of cumulative chemical exposure. Exposure patterns of chemicals may help the reproductive health assessment of adult men.